Intermittent fasting - a diet to fight type 2 diabetes and obesity - current state of knowledge - Mazurek, Joanna; Stachowicz, Hubert; Adamczyk, Monika; Baran, Aleksandra; Bartos, Weronika; Ptasznik, Magdalena; Piotrowska-Żołnierczuk, Magdalena; Podrażka, Miłosz; Lenart, Justyna; Flegiel, Ewelina (Journal of Education, Health and Sport, 2024)
Obesity is a chronic disease that requires diagnosis and treatment. Excess body fat and metabolic disorders, resulting from the disease, are associated with the risk of numerous complications. Among the most widespread are type 2 diabetes, hypertension, dyslipidemia, atherosclerosis, non-alcoholic fatty liver disease and sleep apnea syndrome. Weight reduction significantly improves prognosis, and can mitigate or even reverse complications. A dietary method gaining popularity recently is intermittent fasting. It involves alternating periods of eating and fasting according to a fixed time schedule. There are different types of diet, differing in the length of the fasting period. Intermittent fasting affects the human body by regulating the diurnal rhythm, inducing metabolic switching, that is switching from using glucose as an energy source to lipid oxidation, and by modulating the composition of the gut microbiota. The effects of the diet, proven in clinical trials, include weight loss, improved glucose tolerance, lowered hemoglobin A1c and insulin levels, and improved tissue sensitivity to insulin. However, there is no evidence supporting the superiority of intermittent fasting over continuous calorie restriction. Intermittent fasting also carries a risk of adverse effects, the most serious of which are hypoglycemic episodes. These occur especially in people with type 2 diabetes and taking diabetes medications. Although intermittent fasting appears to be a promising strategy in the fight against obesity and type 2 diabetes, further research is needed to evaluate its long-term effects on the human body.